The roles of toxin A and toxin B in Clostridium difficile infection: Insights from the gnotobiotic piglet model - Steele, Jennifer (Landes Bioscience, 2014)
We recently published our findings indicating that anti-TcdB antibodies were effective as treatment for C. difficile infection, but that anti-TcdA actually worsened prognosis in the gnotobiotic piglet model. To further investigate the roles of the two toxins, we administered purified toxins separately or together, systemically, to piglets and found that both toxins, either alone or together, are able to elicit severe lesions systemically and are also able to cross into the gut lumen and cause large intestinal lesions typical of infection. We also found that anti-TcdA administered before systemic challenge with TcdA again did not protect from development of disease, but, in this case, did not appear to worsen prognosis. Further work is still needed, but these findings add to the growing knowledge regarding the roles of the C. difficile toxins.